Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/2045-7022-3-12
|View full text |Cite
|
Sign up to set email alerts
|

The acute and long‐term management of food allergy: protocol for a rapid systematic review

Abstract: BackgroundAllergic reactions to plant and animal derived food allergens can have serious consequences for sufferers and their families. The associated social, emotional and financial costs make it a priority to understand the best ways of managing such immune-mediated hypersensitivity responses. Conceptually, there are two main approaches to managing food allergy: those targeting immediate symptoms and those aiming to support long-term management of the condition. The European Academy of Allergy and Clinical I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Experts in the field were contacted for additional studies. Further details are included in the review protocol .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experts in the field were contacted for additional studies. Further details are included in the review protocol .…”
Section: Methodsmentioning
confidence: 99%
“…The review was registered with the International Prospective Register of Systematic Reviews. The protocol has been published previously (5) so only brief details about the methodology are provided here.…”
Section: Protocol and Registrationmentioning
confidence: 99%
“…However, there is evidence for the use of hydrolysed formulas in preventing food allergies in infants who cannot be completely breast milk-fed. (43,44) A study from Singapore has shown that consuming probiotics in the first six months of life does not impact allergic outcomes. (45) The timing of introduction of complementary solids in infancy is a persistent source of contention in allergy prevention.…”
Section: Pr E V Entio N O F Foo D a Llergymentioning
confidence: 99%
“…The guideline is based on the current European Academy of Allergy and Clinical Immunology (EAACI) S3-guideline on the diagnosis and treatment of food allergy [ 11 ], as well as on systematic EAACI reviews [ 12 , 13 ] from 2014, for which systematic literature searches of PubMed, meta-analyses, clinical studies, and other scientific investigations were undertaken. Consensus on the present guideline was achieved independently from the European guidelines by an interdisciplinary panel of German-speaking experts who were nominated by the participating societies.…”
Section: Preamblementioning
confidence: 99%